The Roman remains of Northern and Eastern France : a guidebook - Bromwich, James (James Stephen), 1940- (Routledge, 2003)
"Precise instructions, carefully designed maps and numerous annotated illustrations ensure that readers will be able to find the places and things they wish to see. As well as guiding visitors to great sites like Lyon with its magnificent ruins, superb Roman museums and immense siphon aqueducts, the book encourages the search for hidden temples, brick kilns and Roman roads, often 'lost' in the forest. The book also offers a comprehensive examination of the area's Roman heritage, interpreting the varied surviving remains and exploring the lifestyles and environment of the Gallo-Roman people."--Jacket